Association of Genetic Variation in the 3'UTR of LHX6, IMMP2L, and AADAC With Tourette Syndrome - Pagliaroli, Luca; Vereczkei, Andrea; Padmanabhuni, Shanmukha Sampath; Tarnok, Zsanett; Farkas, Luca; Nagy, Peter; Rizzo, Renata; Wolanczyk, Tomasz; Szymanska, Urszula; Kapisyzi, Mira; Basha, Entela; Koumoula, Anastasia; et al. (Frontiers in Neurology, 2020)
Background: Tourette Syndrome (TS) is a neurodevelopmental disorder that presents with motor and vocal tics early in childhood. The aim of this study was to investigate genetic variants in the 3’ untranslated region (3’UTR) of TS candidate genes with a putative link to microRNA (miRNA) mediated regulation or gene expression. Methods: We used an in silico approach to identify 32 variants in the 3’UTR of 18 candidate genes putatively changing the binding site for miRNAs. In a sample composed of TS cases and controls (n=290), as well as TS family trios (n=148), we performed transmission disequilibrium test (TDT) and meta-analysis. Results: We found positive association of rs3750486 in the LIM homeobox 6 (LHX6) gene (p=0.021) and rs7795011 in the inner mitochondrial membrane peptidase subunit 2 (IMMP2L) gene (p=0.029) with TS in our meta-analysis. The TDT showed an over-transmission of the A allele of rs1042201 in the arylacetamide deacetylase (AADAC) gene in TS patients (p=0.029). Conclusions: This preliminary study provides further support for the involvement of LHX6, IMMP2L and AADAC genes, as well as epigenetic mechanisms, such as altered miRNA mediated gene expression regulation in the etiology of TS.